The developmental biology of Charnia and the eumetazoan affinity of the Ediacaran rangeomorphs - Dunn, FS; Liu, AG; Grazhdankin, DV; Vixseboxse, P; Flannery-Sutherland, J; Green, E; Harris, S; Wilby, PR; Donoghue, PCJ (American Association for the Advancement of Science, 2021)
Molecular timescales estimate that early animal lineages diverged tens of millions of years before their earliest unequivocal fossil evidence. The Ediacaran macrobiota (~574 to 538 million years ago) are largely eschewed from this debate, primarily due to their extreme phylogenetic uncertainty, but remain germane. We characterize the development of Charnia masoni and establish the affinity of rangeomorphs, among the oldest and most enigmatic components of the Ediacaran macrobiota. We provide the first direct evidence for the internal interconnected nature of rangeomorphs and show that Charnia was constructed of repeated branches that derived successively from pre-existing branches. We find homology and rationalize morphogenesis between disparate rangeomorph taxa, before producing a phylogenetic analysis, resolving Charnia as a stem-eumetazoan and expanding the anatomical disparity of that group to include a long-extinct bodyplan. These data bring competing records of early animal evolution into closer agreement, reformulating our understanding of the evolutionary emergence of animal bodyplans.